Eosinophilic Solid and Cystic Renal Cell Carcinoma (ESC RCC): Further Morphologic and Molecular Characterization of ESC RCC as a Distinct Entity. (October 2017) - Trpkov, Kiril; Abou-Ouf, Hatem; Hes, Ondřej; Lopez, Jose I.; Nesi, Gabriella; Comperat, Eva; Sibony, Mathilde; Osunkoya, Adeboye O.; Zhou, Ming; Gokden, Neriman; Leroy, Xavier; Berney, Daniel M.; et al.
Abstract : Eosinophilic solid and cystic renal cell carcinoma (ESC RCC) has been recently described as a unique and indolent renal neoplasm, found in female patients with and without tuberous sclerosis complex. Although ESC RCC has a distinct morphology and frequent CK20 reactivity, its molecular karyotype has been previously studied only in few cases. We identified 19 ESC RCC from multiple institutions; all patients were female individuals without clinical features of tuberous sclerosis complex. Molecular karyotyping was performed in 13 cases (12 with informative result). The median age was 55 years (range: 32 to 79 y). The tumors were yellow-gray with a median size of 31 mm (range: 12 to 135 mm) and showed solid and cystic gross appearance. All tumors demonstrated typical microscopic features with solid areas admixed with variably sized macrocysts and microcysts. The cells showed eosinophilic cytoplasm with granular cytoplasmic stippling and round-to-oval nuclei. CK20 was positive in 14/19 (74%) cases. Stage pT1 was found in 17/19 (89%) patients (pT1a in 12, pT1b in 5); 1 patient each had pT2a and pT3a. A total of 15/16 patients with available follow-up were alive and without evidence of disease progression, after 1 to 169 months (median: 44 mo; mean: 49.6 mo); 3 died of other causes. The most common copy number gains were 16p13.3-16q23.1 (33% to 67%), 7p21.2-7q36.2 (42% to 50%), 13q14.2 (33%), and 19p12 (33%). The most common copy number losses included Xp11.21 (42%) and 22q11.23 (33%). Loss of heterozygosity was most frequently found at 16p11.2-11.1 (75%), Xq11.1-13.1 (75%), Xq13.1-21.1 (33%), 11p11.2-11.11 (33%), 9q21.1-22.2 (33%), and 9q33.1 (33%). ESC RCC demonstrates common molecular karyotype alterations, which further support its distinct nature. Abstract : Supplemental Digital Content is available in the text.